The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/fluids5010030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flow Rate on Mesenchymal Stem Cell Oxygen Consumption Rates in 3D Bone-Tissue-Engineered Constructs Cultured in Perfusion Bioreactor Systems

Abstract: Bone grafts represent a multibillion-dollar industry, with over a million grafts occurring each year. Common graft types are associated with issues such as donor site morbidity in autologous grafts and immunological response in allogenic grafts. Bone-tissue-engineered constructs are a logical approach to combat the issues commonly encountered with these bone grafting techniques. When creating bone-tissue-engineered constructs, monitoring systems are required to determine construct characteristics, such as cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…To overcome the diffusion limitation, various perfusion bioreactors have been developed over the years 6,10–18 . An example of a perfusion bioreactor is hollow fibre membrane bioreactors (HFMBs) 5,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the diffusion limitation, various perfusion bioreactors have been developed over the years 6,10–18 . An example of a perfusion bioreactor is hollow fibre membrane bioreactors (HFMBs) 5,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Most probably, this is due to decreasing flow velocities (see Supplementary Figure 1). Supporting this hypothesis, Felder et al showed that the OC of mesenchymal stem cells decreases with lower flow rates (Felder et al, 2020[ 17 ]). Rennert et al demonstrated that higher perfusion rates lead to a higher total OC in a liver-on-a-chip platform (Rennert et al, 2015[ 42 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the application of the millifluidic compartmentalization turned out to be a useful tool in examining both the h-TM cell behavior after exposure to hydrogen peroxide, as an oxidative stressor, and in enabling the analysis of the complex interactions between h-TM cells and their micro environmental components through an accurate and reproducible model. In fact, the limits of 3Dstatic systems are mainly related to a lack of oxygen availability [27], whereas the dynamic millifluidic platform provides a constant flow rate of the culture medium within the whole bioreactor circuit, allowing a continuous nutrient supply of oxygen to the connected multi-culture chambers, and thus overcoming not only the mass transport limitations, but also removing the metabolic products from the cells.…”
Section: Introductionmentioning
confidence: 99%